Current syphilis infection in virally suppressed people living with HIV: a cross-sectional study in eastern China - He, Lin; Pan, Xiaohong; Yang, Jiezhe; Zheng, Jinlei; Luo, Mingyu; Cheng, Wei; Chai, Chengliang (Frontiers in Public Health, 2024)
Background: Antiretroviral therapy (ART) has been shown to reduce human immunodeficiency virus (HIV) viral replication and ultimately achieve viral suppression and eliminate HIV transmission. However, little is known about the impact of viral suppression on high-risk behaviors and sexually transmitted infections (STIs).Objective: This study aimed to assess the rates of current syphilis infection in virally suppressed people living with HIV (PLWH) and whether with the duration of ART can reduce the current syphilis infection in Eastern eastern China.We conducted a cross-sectional survey of PLWH in Zhejiang Province, China, in 2022. PLWH who were on ART 6 months and were virally suppressed (viral load <50 copies/mL) were included in the study. Data were collected from the National Epidemiological Database of Zhejiang Province and all participants were tested for viral load and current syphilis. Multivariable logistic regression was used to identify risk factors associated with current syphilis infection.Result: A total of 30,744 participants were included in the analysis. 82.7% of participants were male, the mean age was 44.9  14.1 years, 84.9% had received ART in a hospital setting, the mean time on ART was 5.9  3.1 years and 5.6% of participants were infected with current syphilis. Multivariable logistic regression showed that being male (adjusted odds ratio [aOR]: 2.12, 95% confidence interval [CI]: 1.69-2.66), high level of education (aOR: 1.23, 95% CI: 1.02-1.49), homosexual route of HIV infection (aOR: 1.80, 95% CI: 1.60-2.04), non-local registered residence (aOR: 1.29, 95% CI: 1.11-1.51), had history of STIs before HIV diagnosis (aOR: 1.95, 95 % CI: 1.75-2.18) and treatment provided by a municipal hospital (aOR: 2.16, 95% CI: 1.31-3.55) were associated with increased risk of current syphilis infection. Being married (aOR: 0.67, 95% CI: 0.58-0.76) was associated with a decreased risk of current syphilis infection.Our findings revealed a high rates of current syphilis infection in among virally suppressed PLWH in Eastern eastern China. With the dDuration of ART did not reduce the prevalence of current syphilis infection. Targeted interventions tothat reduce current syphilis infection should be prioritized for subgroups at higher risk.